2015
DOI: 10.1136/bcr-2015-209948
|View full text |Cite
|
Sign up to set email alerts
|

Pilonidal sinus involving the nasal bridge: a rare manifestation

Abstract: SUMMARYPilonidal sinus is very commonly associated with the sacrococcygeal area, but its presence within the head and neck is still unknown to many. Once diagnosed, it is easy to treat and should, therefore, be kept in mind as a possibility when coming across a discharging sinus swelling. We share our experience of two cases of pilonidal sinus presenting over the nasal bridge and their management. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(13 reference statements)
0
5
0
1
Order By: Relevance
“…Although formation of the sinus is mostly observed in those in their early 20s, it is, rarely, observed in those over the age of 45 years 10. Pilonidal sinus on the face area was reported to be on the ear,5 nose6 7 and scalp 8. But our case is the second after that by Oudit et al ,3 to be reported on the chin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although formation of the sinus is mostly observed in those in their early 20s, it is, rarely, observed in those over the age of 45 years 10. Pilonidal sinus on the face area was reported to be on the ear,5 nose6 7 and scalp 8. But our case is the second after that by Oudit et al ,3 to be reported on the chin.…”
Section: Discussionmentioning
confidence: 99%
“…Pilonidal sinus has also been reported on the face,4 ear,5 nose6 7 and scalp 8. There are also some reports of its existence in the interdigital clefts of barbers’ fingers 9.…”
Section: Introductionmentioning
confidence: 98%
“…Der Pilonidalsinus tritt vornehmlich in der Rima ani auf, wird aber auch im Nabelbereich [106,170,175,247,316], inter-und submammillär [422], an Vulva, Mons pubis und Klitoris, [212,213,239], Penis [268,350], Anus [365,452], interdigital (z. B. bei Friseuren; [57,168,376,447]), an der Fingerspitze [198] im Bereich der Brust [176] und auch im Bereich der Nase [238] und hinter den Ohren gesehen [485]. Die Berufsgruppe der Friseure ist ausschließlich an ihrer Körpervorderseite multiplen Haareinspießungen ausgesetzt [137].…”
Section: Lokalisationunclassified
“…In recent studies, acquired factors were known responsible for the etiopathogenesis of the disease (1). Although the common site of disease is the sacrococcygeal region, some reports in the umbilicus (3), breast (4), intermammary (5), axillary (6), penis, vulvae (7), and nasal bridge (8) have also been reported with unignorable potentially incidentally finding of malignancy in the lesion (9). History and physical examination are usually sufficient for diagnosis, although the role of sonography in the better detection of lesion was reported in some studies (10).…”
Section: Introductionmentioning
confidence: 99%